2017
DOI: 10.1055/s-0043-105262
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gall Bladder Wall Thickening in Dengue Fever: A Mirror of the Severity of Disease

Abstract: Background Dengue fever is a major public health problem with an increased incidence in recent years. Gall bladder wall thickening has been reported as one of the most common findings in dengue fever. There is a paucity of literature regarding the various patterns of gall bladder wall thickening in dengue fever and their significance in predicting the severity of disease. Methodology and Significant Findings Out of 93 seropositive patients included in the study, 54 patients with dengue fever had gall bladder w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 8 publications
4
25
0
Order By: Relevance
“…These ndings were in accordance with a similar study done by Michels M et al in which severe dengue patients had a gallbladder wall thickening of 3-7 mm and the non-severe cases had a mean value of 3.6 mm [15]. Jitendra et al had a similar study with mean GB wall thickness of 3.32-4.95 mm in non-severe dengue cases and a mean value 8.8 mm among severe dengue cases [16]. Our ndings were consistent with the clinical deterioration of patients with non-severe dengue on the 3rd − 4th day of fever to severe dengue as the days progressed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These ndings were in accordance with a similar study done by Michels M et al in which severe dengue patients had a gallbladder wall thickening of 3-7 mm and the non-severe cases had a mean value of 3.6 mm [15]. Jitendra et al had a similar study with mean GB wall thickness of 3.32-4.95 mm in non-severe dengue cases and a mean value 8.8 mm among severe dengue cases [16]. Our ndings were consistent with the clinical deterioration of patients with non-severe dengue on the 3rd − 4th day of fever to severe dengue as the days progressed.…”
Section: Discussionsupporting
confidence: 91%
“…Clinically it is di cult to determine leakage of plasma and quite often serum hematocrit is used as an adjunct to detect signi cant plasma leak [15]. Gallbladder wall thickening due to signi cant plasma leakage is one of the commonest ndings in dengue fever [16]. A few studies indicate that ultrasonography plays an important role in detecting patients who progress to a critical phase by measuring the thickness of the gallbladder wall [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, serial ultrasounds were performed on consecutive alternate days, which revealed change in the pattern of gall bladder wall thickening according to the severity of disease, clearly establishing gall bladder wall thickening due to dengue fever only [1].…”
mentioning
confidence: 53%
“…In GB wall oedema there is preservation of mucosal echogenicity with hypoechoic appearance of muscle layer. There are 4 patterns of GB wall thickening described in Dengue fever [6]. They are A) Uniform wall thickening; B) Tram -track pattern; C) Asymmetric wall thickening; D) Honeycomb pattern.…”
Section: Discussionmentioning
confidence: 99%